2013
DOI: 10.1200/jco.2012.46.2408
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized Phase II Study of the Anti–Epidermal Growth Factor Receptor Monoclonal Antibody Cetuximab With Cisplatin Versus Cisplatin Alone in Patients With Metastatic Triple-Negative Breast Cancer

Abstract: Purpose Epidermal growth factor receptor is overexpressed in metastatic triple-negative breast cancers (mTNBCs), an aggressive subtype of breast cancer. Our randomized phase II study investigated cisplatin with or without cetuximab in this setting. Patients and Methods Patients who had received no more than one previous chemotherapy regimen were randomly assigned on a 2:1 schedule to receive no more than six cycles of cisplatin plus cetuximab or cisplatin alone. Patients receiving cisplatin alone could switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
245
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(254 citation statements)
references
References 29 publications
6
245
0
3
Order By: Relevance
“…Recently, however, EGFR-targeting monoclonal antibody, cetuximab, has improved outcomes in triple-negative breast cancers. 24 EGFR gene amplification, one of the mechanisms of EGFR overexpression, is highly variable and found in up to 24% of triple-negative breast cancer. 10,11,13,14,19,25 EGFR gene mutation, another mechanism of EGFR overexpression, has been reported to be rare, 11,17,19,25,26 although a recent study reported that it was present in 11% of triplenegative breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, EGFR-targeting monoclonal antibody, cetuximab, has improved outcomes in triple-negative breast cancers. 24 EGFR gene amplification, one of the mechanisms of EGFR overexpression, is highly variable and found in up to 24% of triple-negative breast cancer. 10,11,13,14,19,25 EGFR gene mutation, another mechanism of EGFR overexpression, has been reported to be rare, 11,17,19,25,26 although a recent study reported that it was present in 11% of triplenegative breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Cetuximab used as monotherapy provided poor response rates [60] , despite the EGFR pathway is active in these patients indicating that alternative pathway activation mechanisms exist in these patients. The addition of cetuximab though to cisplatin improved responses in the metastatic setting in comparison to cisplatin monotherapy despite the study did not met predefined criteria for OS and PFS [61] indicating that EGFR inhibition could have therapeutic benefit in these patients. Another EGFR inhibitor, erlotinib, has also shown encouraging pCR rates when combined with Carboplatin-Docetaxel chemotherapy in a small phase II trial [62] .…”
Section: Novel Agents In the Neoadjuvant Treatment Of Tnbcmentioning
confidence: 95%
“…Development of new HER2-targeted therapies, including antibody-delivered cytotoxins and chimeric antigenbased immune cell repertoires, has shown promise in both research and clinical settings (14,15,(30)(31)(32). However, while clinical targeting of EGFR function through small molecule inhibitors or antibody inhibition of EGFR signaling has shown some promise, successful long-term outcomes are rare because of compensatory kinase domain mutations or alternate receptor signaling and problems with toxicity to normal tissue (33)(34)(35)(36). As ITs target protein synthesis rather than receptor signaling pathways, mutations in the receptor active site or alternate signaling pathways should not affect the activity of this therapeutic.…”
Section: Discussionmentioning
confidence: 99%